ANALISIS RAGAM GENOTIP RAPD DAN FENOTIP TRUSS MORFOMETRIK PADA TIGA POPULASI IKAN GABUS - Rudhy Gustiano; Tia Oktaviani; Dinar Tri Soelistyowati; Irin Iriana Kusmini; Wahyutomo Wahyutomo; Gleni Hasan Huwoyon (BERITA BIOLOGI, 2013)
In order to manage genetic resources for aquaculture development of snakehead fishChannastriata(Bloch, 1793), genetic variability of three populations from different geographical areas is needed to be understood. The purpose of this study was to identify the genotype and fenotype of snakehead fish from Jawa, Sumatera and Kalimantan using RAPD and “Truss” morphometric. RAPD method used OPA-02, OPA-04 and OPA-07 primers.While twenty one measurement of truss morphometric was done on the body of fish observed. The results showed that population from Java had higher percentage of polymorphism and heterozygosity than those of Sumatera and Kalimantan, accounted for 83.33% and 0.3655 respectively. Population from Kalimantan and Sumatera had the lowest genetic distance of 0.1170.Meanwhile,the highest genetic distance (0.1908) was observed between population from Kalimantan and Java.Interpopulation relation based on the similarity of truss morphometric population from Sumatera and Kalimantan was 50%. However, those populations had similarity of 24.96% with population from Java. Coefficient variation of morphometric data showed that variation of population from Kalimantan was higher than those of Jawa and Sumatera.